Les trajectoires en bouleversement d’un vieux quartier d’immigration à Paris : une approche micro-géographique - Marie Chabrol; Anouche Kunth (Diasporas: Circulations, Migrations, Histoire)
This discussion with the geographer Marie Chabrol, is devoted to the in-depth mutations taking place in Château-Rouge, an old immigrant neighbourhood of Paris internationally known for being a major African commercial centrality in a European city. She emphasizes her interest in the urban temporalities and individual trajectories and talks about the influence of microstoria on her own work at a theoretical level.